Does mood affect trading behavior? - Markku Kaustia; Elias Rantapuska (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
We test whether investor mood affects trading with data on all stock market transactions in Finland, utilizing variation in daylight and local weather. We find some evidence that environmental mood variables (local weather, length of day, daylight saving and lunar phase) affect investors' direction of trade and volume. The effect magnitudes are roughly comparable to those of classical seasonals, such as the Monday effect. The statistical significance of the mood variables is weak in many cases, however. Only very little of the day-to-day variation in trading is collectively explained by all mood variables and calendar effects, but lower frequency variation seems connected to holiday seasons.
urn:nbn:de:hebis:30:3-293731
Keywords: D03; G11; G12; 330; mood; seasonal affective disorder (SAD); weather; trading behavior; stock market